FORMATION OF OMNICAL MARKETING STRATEGIES IN RETAIL TRADE (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article considers the role of e-commerce in our time. The world tendencies of online trade development are determined. It is emphasized that large investments are being made in e-commerce, contactless opportunities and other technology updates. The development of e-commerce in Ukraine is studied and the main economic indicators of its development are analyzed. The main problems of e-shopping in Ukraine are named: fear of mistakes, lack of trust in online stores, lack of need for online shopping and the desire to see the product before buying. The evolution of trade development from offline to online sales is shown. It was noted that the impetus for the growth of online commerce in Ukraine is the government's approval of an action plan to create conditions for the development of mobile broadband access. The dynamics of innovation in retail communications is studied. It is emphasized that in a world of fierce competition, business efforts to innovate to maintain and increase customer loyalty are rapidly moving to the norm instead of the wow effect, so to run a successful business you need to know your customers. audience and change with it. To do this, you need to understand what people live, what they choose and with whom they compare. Factors influencing changes in consumer buying behavior under the influence of such factors as the growth of digitalization of society and the consequences of the pandemic have been identified. An omnipotent marketing strategy of a retail trade enterprise has been developed. Examples of Watsons and Comfy that successfully use the omnichannel model are described. It is concluded that a successful omni-channel strategy puts the consumer in the spotlight, providing ideal conditions for shopping using different channels, platforms and tools, so the success of retail is to build a relationship with the consumer that withstands the test of time and bring in revenue through consistent customer loyalty, whether it's an online sale or a regular store purchase.
Keywords: retail, online sales, offline sales, omnic marketing strategy, consumer